Metode Tafsir Muhammad Abduh dan Muhammad Rasyid Ridha dalam Tafsîr Al-Manâr - Kharlie, Ahmad Tholabi (TAJDID, 2018)
Tafsîr al-Manar is one of the most popular exegesis of the Qur`anic studies. Al-Manar magazine, which contains this interpretation periodically, namely in the early 20th century, is widespread throughout the Islamic world and has an important role in enlightening thoughts and religious counseling. The influence of Sheikh Muhammad Abduh, along with his student, Sayyid Muhammad Rasyîd Ridhâ, on the development of religious thought in the Islamic world, thus, cannot be underestimated.This article is a result of a previous study of the Qur’an exegesis method of the two prominent Muslim scholars, Muhammad Abduh and Muhammad Rashid Ridha. The study reveals two main conclusions, they are (1) personally both Muhammad Abduh and Muhammad Rashid Ridha are independent who have extensive, well-known, and versatile insight and knowledge, have personality traits that are steady, honest, brave, passionate, intelligent, determined, and a number of other advantages, like other leading commentator (2) Al-manâr book, with its superiorities, is well recognized as a monumental work that broadly contributes to the development of Islamic thought, particularly in modern exegesis field. In regard to exegesis of Qur’anic legal verses, though it is not a special legal book, Al-manâr is able to explain deeply and comprehensively the Qur’anic legal verses just like the other legal exegesis works.